Fuzzy multi-objective production/distribution planning decisions with multi-product and multi-time period in a supply chain - Liang, Tien-Fu (Computers & industrial engineering, 2008)
This work develops a fuzzy multi-objective linear programming (FMOLP) model with piecewise linear membership function to solve integrated multi-product and multi-time period production/distribution planning decisions (PDPD) problems with fuzzy objectives. The original multi-objective linear programming designed in this work model attempts to simultaneously minimize total costs and total delivery time in relation to inventory levels, available machine capacity and labor levels at each source, and forecast demand and available warehouse space at each destination and total budget. The proposed FMOLP model provides a systematic framework that facilitates fuzzy decision-making process, enabling the decision maker (DM) to interactively adjust the search direction during the solution procedure to obtain a DM’s preferred satisfactory solution. Additionally, the DM computes the value in each cost category by considering the time value of money in the proposed model, which is appropriate for practical application to the PDPD problem in a supply chain. Finally, an industrial case demonstrates the feasibility of applying the proposed model to a real-world integrated PDPD problem in a supply chain under uncertain environments.